EFFICIENCY ENHANCEMENT IN THE RECUPERATOR OF A REHEATING FURNACE - Alper Güneç; Meliha Rigan; Elif Mendi; Ali Osman Aydınnarı; Sena Ozal (MATTER: International Journal of Science and Technology, 2025)
In today’s world, increasing environmental concerns have intensified the focus on renewable energy sources and effective energy management practices. In industrial processes, particularly in areas with high energy consumption, waste heat recovery has become one of the primary research topics. Reheating furnaces used in the steel industry reach extremely high temperatures during rolling operations, with approximately 50–70% of this energy being released directly into the atmosphere through flue gases. In this context, flue gases stand out as one of the most significant sources of waste heat. The aim of this study is to recover the waste energy contained in the flue gases emitted to the atmosphere from a slab reheating furnace used in the hot rolling process of the iron and steel industry by means of a recuperator. Through the newly implemented recuperator replacement, 31,274.93 kW of energy recovery was achieved and 6.32 tons of carbon emissions were reduced. Consequently, the amount of energy released into the atmosphere was decreased, and a significant reduction in natural gas consumption of the furnace was obtained.